How do international lawyers handle facts?: The role of folk sociological theories at the International Criminal Court - Seroussi, Julien (The British journal of sociology, 2019)
The International Criminal Court (ICC) investigates international crimes committed in different parts of the world. Earlier scholarly analysis of the work performed by the ICC judges has pointed out that judges often lack cultural and national understanding of the local norms and customs of regions where defendants come from. This article treats this lack of contextual knowledge displayed by the court as a case of structural ignorance rather than an aberration to be ‘exposed’ or censured. International lawyers indeed must ground their legal narratives with plausible sociological explanations of contextual elements to overcome their lack of familiarity with the field and the scarcity of their investigative resources. By uncovering the role of ‘folk sociological theories’ (FSTs) in the establishment of facts in a court context, this article addresses the debate over the efficiency of international criminal justice by highlighting the need to bring historical truth back in. The empirical evidence is based on several years of participant observation in the ICC during the trials against Mathieu Ngudjolo and Germain Katanga, two militiamen from the Democratic Republic of Congo (DRC).